Kohesi dan Koherensi Berita Surat Kabar Online Wonosobo Zone Edisi September - November 2024 - Riyan Prasetyo; Mursia Ekawati (Jurnal Bima : Pusat Publikasi Ilmu Pendidikan Bahasa dan Sastra, 2024)
Research This study aims to analyze cohesion and coherence in the news of Wonosobo Zone online newspaper. Wonosobo Zone online newspaper from September to November 2024. Cohesion refers to cohesion between linguistic elements in the text, while coherence refers to the logical integration of meaning between ideas. to the logical integration of meaning between ideas. This research uses qualitative approach with a text analysis method, where data in the form of news published during the published during the period were analyzed using cohesion and coherence. coherence. The results showed that the news analyzed generally have a good level of cohesion through the use of devices such as reference, conjunction, and lexical devices. There is marked coherence, namely coherence of intensity, causality and contrast. This study concludes that good quality of cohesion and coherence is needed to increase the effectiveness of news communication to readers. news communication to readers. The results of the study can serve as a reference for improving the quality of news writing in local online newspapers.